KONSEP PENDIDIK DAN PESERTA DIDIK DALAM ISLAM(TELAAH KITAB ADABUL ‘ALIM WAL MUTA’ALLIM KARYA KH. HASYIM ASY’ARI) - Fatihul Khoir (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Education is one of the most important things in the process of human life, this education is an effort to develop and nurture all aspects of the human personality so that they become better. Education is a forum for forming a complete human being who is able to compete with other humans both in academic and non- academic matters. In order for the educational process to run well, educators and students must have good characteristics that are based on the teachings of the Islamic religion. The Book of Adabul 'Alim Wal Muta'allim by KH. Hasyim Asy'ari can be used as a guide for educators and students in the current education process, so that educators and students have good guidelines. This research uses library research, by collecting data based on library texts. in the form of books, journals and other scientific works that are relevant to the research discussion. The results of this research are that the Educator's Concept in the Book of Adabul 'Alim Wal Muta'allim is Purifying intentions, having qana'ah characteristics in all aspects of life, Behaving Tawadhu', being ascetic in his life, and avoiding all forms of immorality around him. Meanwhile, the concept of students in the Book of Adabul 'Alim Wal Muta'allim is that a student should purify his heart from all forms of immorality, improve his intentions in seeking knowledge, not delay in seeking knowledge, act qana'ah, act wira'i, ask Allah for guidance. SWT so that the right teacher is chosen, looking at the teacher with full admiration and ta'dzim respect.